1983
DOI: 10.1172/jci110804
|View full text |Cite
|
Sign up to set email alerts
|

Effect of synthetic ovine corticotropin-releasing factor. Dose response of plasma adrenocorticotropin and cortisol.

Abstract: A B S T R A C T Synthetic ovine corticotropin-releasing factor (CRF) was administered to normal male volunteer subjects as an intravenous bolus or 30-s infusion. Doses of CRF ranging from 0.001 to 30 sg/kg body wt were administered, and plasma immunoreactive (IR)-ACTH and IR-cortisol concentrations were measured. The threshold dose appeared to be 0.01-0.03 ag/kg, the half-maximal dose 0.3-1 sg/kg, and the maximally effective dose 3-10 ug/kg. Basal concentrations of IR-ACTH and IR-cortisol were 14±7.6 pg/ ml (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
72
0
4

Year Published

1984
1984
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(84 citation statements)
references
References 29 publications
(43 reference statements)
8
72
0
4
Order By: Relevance
“…In humans, ovine CRF (oCRF), which is the commercially available CRF used in clinical diagnostics, has a longer plasma half-life (73 min) than human CRF (hCRF) (27 min) (eg Saphier et al, 1992). Dose-response studies of oCRF, which differs by 7 amino acids from hCRF, using doses of 0.001-30 mg/kg (Orth et al, 1983) and hCRF using doses of 0.01-5 mg/kg (Schurmeyer et al, 1984) have demonstrated an apparent maximal response in cortisol at doses above 3.0 and 1.0 mg/kg, respectively. However, neither of these studies, nor any other published dose-response studies of oCRF or hCRF, achieved a maximal response (ie no plateau reached) in ACTH to the highest administered doses of CRF.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, ovine CRF (oCRF), which is the commercially available CRF used in clinical diagnostics, has a longer plasma half-life (73 min) than human CRF (hCRF) (27 min) (eg Saphier et al, 1992). Dose-response studies of oCRF, which differs by 7 amino acids from hCRF, using doses of 0.001-30 mg/kg (Orth et al, 1983) and hCRF using doses of 0.01-5 mg/kg (Schurmeyer et al, 1984) have demonstrated an apparent maximal response in cortisol at doses above 3.0 and 1.0 mg/kg, respectively. However, neither of these studies, nor any other published dose-response studies of oCRF or hCRF, achieved a maximal response (ie no plateau reached) in ACTH to the highest administered doses of CRF.…”
Section: Discussionmentioning
confidence: 99%
“…In man, ovine CRF (oCRF) is a potent stimulus to ACTH secretion (5) and has a prolonged duration of action (6) that is probably due to its prolonged circulating half-life in plasma (7).…”
Section: Introductionmentioning
confidence: 99%
“…The negative CRF test before adenomectomy remains unexplained, as there is usually a significant increase of ACTH and cortisol within the first hour of the test in patients with central CS [2,6,7,9]. Improper application of CRF is an unlikely explanation, since the patient showed the usual symptoms of flush and heat waves during both tests [7,9].…”
Section: Discussionmentioning
confidence: 99%
“…Improper application of CRF is an unlikely explanation, since the patient showed the usual symptoms of flush and heat waves during both tests [7,9].…”
Section: Discussionmentioning
confidence: 99%